Looking for trustworthy answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Connect with a community of experts ready to help you find accurate solutions to your questions quickly and efficiently. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
Certainly! Let's walk through solving [tex]\( p = \binom{-6}{1} \)[/tex] and [tex]\( q = \binom{13}{14} \)[/tex] first, and then we will calculate [tex]\( 4p + q \)[/tex].
### Step 1: Calculating [tex]\( p = \binom{-6}{1} \)[/tex]
The binomial coefficient [tex]\(\binom{n}{k}\)[/tex] is typically defined for non-negative integers [tex]\(n\)[/tex] and [tex]\(k\)[/tex] such that [tex]\(0 \leq k \leq n\)[/tex]. However, it can also be extended to include cases where [tex]\(n\)[/tex] can be a negative integer using the general formula for binomial coefficients:
[tex]\[ \binom{n}{k} = \frac{n(n-1)(n-2)\cdots(n-k+1)}{k!} \][/tex]
For [tex]\( n = -6 \)[/tex] and [tex]\( k = 1 \)[/tex]:
[tex]\[ \binom{-6}{1} = \frac{-6}{1!} = -6 \][/tex]
So, [tex]\( p = -6 \)[/tex].
### Step 2: Calculating [tex]\( q = \binom{13}{14} \)[/tex]
For any binomial coefficient [tex]\(\binom{n}{k}\)[/tex] where [tex]\( k > n \)[/tex], the value is 0 because there are no ways to choose more elements than are available:
[tex]\[ \binom{13}{14} = 0 \][/tex]
So, [tex]\( q = 0 \)[/tex].
### Step 3: Calculating [tex]\( 4p + q \)[/tex]
Now we combine the results:
[tex]\[ 4p + q = 4(-6) + 0 = -24 + 0 = -24 \][/tex]
### Step 4: Writing the answer as a column vector
The final answer as a column vector:
[tex]\[ \begin{pmatrix} -24 \end{pmatrix} \][/tex]
Thus, [tex]\( 4p + q = \begin{pmatrix} -24 \end{pmatrix} \)[/tex].
### Step 1: Calculating [tex]\( p = \binom{-6}{1} \)[/tex]
The binomial coefficient [tex]\(\binom{n}{k}\)[/tex] is typically defined for non-negative integers [tex]\(n\)[/tex] and [tex]\(k\)[/tex] such that [tex]\(0 \leq k \leq n\)[/tex]. However, it can also be extended to include cases where [tex]\(n\)[/tex] can be a negative integer using the general formula for binomial coefficients:
[tex]\[ \binom{n}{k} = \frac{n(n-1)(n-2)\cdots(n-k+1)}{k!} \][/tex]
For [tex]\( n = -6 \)[/tex] and [tex]\( k = 1 \)[/tex]:
[tex]\[ \binom{-6}{1} = \frac{-6}{1!} = -6 \][/tex]
So, [tex]\( p = -6 \)[/tex].
### Step 2: Calculating [tex]\( q = \binom{13}{14} \)[/tex]
For any binomial coefficient [tex]\(\binom{n}{k}\)[/tex] where [tex]\( k > n \)[/tex], the value is 0 because there are no ways to choose more elements than are available:
[tex]\[ \binom{13}{14} = 0 \][/tex]
So, [tex]\( q = 0 \)[/tex].
### Step 3: Calculating [tex]\( 4p + q \)[/tex]
Now we combine the results:
[tex]\[ 4p + q = 4(-6) + 0 = -24 + 0 = -24 \][/tex]
### Step 4: Writing the answer as a column vector
The final answer as a column vector:
[tex]\[ \begin{pmatrix} -24 \end{pmatrix} \][/tex]
Thus, [tex]\( 4p + q = \begin{pmatrix} -24 \end{pmatrix} \)[/tex].
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.